Morel (Morchella spp.) intake alters gut microbial community and short-chain fatty acid profiles in mice - Pei, Longying; Liu, Wei; Liu, Luping; Wang, Xiaoyu; Jiang, Luxi; Chen, Zhaohui; Wang, Qiquan; Wang, Peng; Xu, Heng (Frontiers in Nutrition, 2023)
Morels (Morchella spp.) are highly nutritious and consumed as both edible mushrooms and traditional Chinese medicine. This study aimed to investigate the effects of dietary supplementation with morel mushrooms on the gut bacterial microbiota and short-chain fatty acids (SCFAs) profiles in healthy mice. Healthy mice were randomly assigned to five groups: a control group (0% morel) and four intervention groups supplemented with different levels of morel mushrooms (5% for M5, 10% for M10, 15% for M15, and 20% for M20) over a period of 4 weeks. Fecal samples were collected at the end of the experiment to characterize the microbiota and assess the SCFAs levels. The morel intervention significantly altered the bacterial community composition, increasing Bacteroides, Lachnospiraceae NK4A136 group and Parabacteroides, while decreasing Staphylococcus and the Firmicutes to Bacteroidetes ratio (F/B ratio). Moreover, increased morel intake was associated with weight loss. All SCFAs content was upregulated in the morel-intervention groups. Potential SCFAs-producing taxa identified by regression analysis were distributed in the families Muribaculaceae, Lachnospiraceae, and in the genera Jeotgalicoccus, Gemella, Odoribacter, Tyzzerella 3 and Ruminococcaceae UCG-014. The functional categories involved with SCFAs-production or weight loss may contain enzymes such as beta-glucosidase (K05349), beta-galactosidase (K01190), and hexosaminidase (K12373) after morel intervention. The exploration of the impact of morel mushrooms on gut microbiota and metabolites contributes to the development of prebiotics for improving health and reducing obesity.